Teaching/learning: The yin and yang of language development from home through school. (21st May 2015) - Martin, Jim
Abstract : In regard to the issues people have been discussing, Jim Martin continues in this article his advocacy for an equal balance between teaching and learning rather than the focus on either side only: the traditional teacher centre and the recent students' centre; in fact, recent years' explorations in this area have to a large extent ignored the role of teaching in students' language learning and development. He takes into consideration of language development from home through school by means of linguistic genres and shared experience, points out the concern about genre teaching, and submits the balance issue to us language teachers.